Organizational behavior : integrating individuals, groups, and organizations - Champoux, Joseph E. (Joseph Edward) (New York : Routledge, 2020)
"The new edition of this essential resource in organizational behavior provides a balanced framework to understand the impact of increasing dynamism and complexity, the importance of collaboration, and the implications for organizational strategy. Covering both psychological and sociological perspectives on organizational behavior, this clearly written and presented textbook offers a comprehensive review of classic organizational behavior theories and approaches, illustrated with updated case studies. The sixth edition includes new material on ethical considerations; international contexts, with renewed attention to Africa and Asia; environmental pressures and responses; groups and intergroup processes; and the vital importance of building change readiness in any organization. Upper-level business and technology students, as well as professionals in executive education courses, will find the book a useful guide to all facets of organizational behavior. A companion website, featuring an instructor manual, test bank, and PowerPoint slides, provides additional support for students and instructors"--
Includes bibliographical references and index.
Keywords: Organizational behavior